Analysis of the sustainability reporting initiatives of electric utilities in Brazil - Camargos, Mariana Rocha (Industrija, 2014)
In an effort to attend to the growing concern about the social and environmental impact of organizational activities, several companies have begun to publish corporate sustainability reports. Brazilian power sector, following a worldwide trend, has the great majority of its companies using the Global Reporting Initiative (GRI) framework as a model for sustainability reporting. A different model of Corporate Social Report is also required, by law, by the Brazilian National Agency of Electric Energy (ANEEL). In this context, we assessed how Brazilian electricity utilities are using GRI guidelines and if the requirements of ANEEL influences the choice of GRI indicators by the companies that report by this model. Our findings show that the adopted sustainability concept, the adequacy to the GRI principles, the choice of indicators and the quality of the information reported is quite variable among different companies. It also became clear the influence of ANEEL in the content of GRI report.